2015
DOI: 10.1007/s11517-015-1288-5
|View full text |Cite
|
Sign up to set email alerts
|

Strength analysis of clavicle fracture fixation devices and fixation techniques using finite element analysis with musculoskeletal force input

Abstract: In the cases, when clavicle fractures are treated with a fixation plate, opinions are divided about the best position of the plate, type of plate and type of screw units. Results from biomechanical studies of clavicle fixation devices are contradictory, probably partly because of simplified and varying load cases used in different studies. The anatomy of the shoulder region is complex, which makes it difficult and expensive to perform realistic experimental tests; hence, reliable simulation is an important com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
1
15
0
3
Order By: Relevance
“…As previous studies [13,14], the screw hole above the fracture site is the weakest point in the superior clavicle locking plate for comminuted midshaft clavicle fracture, especially in the cantilever bending force. B model showed superior biomechanical property than A model under all loading conditions.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As previous studies [13,14], the screw hole above the fracture site is the weakest point in the superior clavicle locking plate for comminuted midshaft clavicle fracture, especially in the cantilever bending force. B model showed superior biomechanical property than A model under all loading conditions.…”
Section: Discussionsupporting
confidence: 52%
“…According to the study which was a FEA about clavicle fracture xation, the maximum stress in the precontoured superior reconstruction plate xation without lag screws occurred at the edge of screw holes above the fracture site [13]. Also other study revealed that the weakest point of the superior clavicle locking compression plate in comminuted midshaft clavicle fracture is the screw holes above fracture zone, especially in the cantilever bending force and therefore recommended a new design which is a superior locking plate without screw holes above fracture zone to prevent metal failure [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to implementing these updated models in vibration-based biomechanical research as stated above, vibration-validated clavicle FE models can also find their application in numerical orthopedic research applications, such as the assessment of clavicle fracture fixation treatments [4,[10][11][12][13][14][15]46], influence of patient-specific parameters on clavicle fractures [47] or analysis of stress shielding effects in clavicle fracture fixation treatments [16].…”
Section: Discussionmentioning
confidence: 99%
“…FE analysis offers the possibility to analyze biomechanical structures while controlling multiple parameters, such as loading/boundary conditions, geometry, material properties etc., contributing to a better insight in the studied problem. More specifically, FE models have found their merit in clavicle-related orthopedic research, such as the assessment of stress, strain and micro-motion distribution in clavicle fracture fixation treatments [4,[10][11][12][13][14][15] or the quantification of stress shielding around clavicle fracture fixation implants [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was decided to use 3D FEM in this study to evaluate the analysis due to its various advantages, such as localizing the stresses on the plate, screws and in every region of the bone and realistic simulation of the plate and screws (7). The aim of stress analysis with FEM is to investigate the weak points when a structural deformation occurs on structures under a load (8,9).…”
Section: Discussionmentioning
confidence: 99%